Current Studies and Future Directions of Exercise Therapy for Muscle Atrophy Induced by Heart Failure - Liu, Qi; Gao, Juan; Deng, Jiali; Xiao, Junjie (Frontiers in Cardiovascular Medicine, 2020)
Muscle atrophy is a common complication of heart failure. At present, there is no specific treatment to reverse the course of muscle atrophy. Exercise training, due to the safety and easy operation, is a recommended therapy for muscle atrophy induced by heart failure. However, the patients with muscle atrophy are weak in mobility and may not be able to train for a long time. Therefore, it is necessary to explore novel targets of exercise protection for muscle atrophy, so as to improve the quality of life and survival rate of patients with muscular atrophy induced by heart failure. This article aims to review latest studies, summarize the evidence and limitations, and provide a glimpse into the future of exercise for the treatment of muscle atrophy induced by heart failure. We wish to highlight some important findings about the essential roles of exercise sensors in muscle atrophy induced by heart failure, which might be helpful for searching potential therapeutic targets for muscle wasting induced by heart failure.